2018
DOI: 10.35609/afr.2018.3.4(2)
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Voluntary Disclosure Before and After the Establishment of the Integrated Reporting Framework

Abstract: Objective - The goal of integrated reporting is to enhance the cohesiveness and efficiency of corporate reporting. It encourages organizations to create greater value by identifying the factors that have a material impact on its operations. The Integrated Reporting (IR) Framework guides the overall content of an integrated report through the Guiding Principles and Content Elements. The Framework has eight elements. This study explores the level of voluntary disclosure of information related to these eight elem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…The rest of the content elements regressed compared to the levels before the release of the 2013 IR framework. The results indicate that there is more work required in the promotion of the adoption of IR in Malaysia, with more collaboration between the reporting regulatory bodies, government and professionals (Jaffar, Nor and Selamat, 2018). c)…”
Section: Ir In Malaysiamentioning
confidence: 91%
See 1 more Smart Citation
“…The rest of the content elements regressed compared to the levels before the release of the 2013 IR framework. The results indicate that there is more work required in the promotion of the adoption of IR in Malaysia, with more collaboration between the reporting regulatory bodies, government and professionals (Jaffar, Nor and Selamat, 2018). c)…”
Section: Ir In Malaysiamentioning
confidence: 91%
“…A comparison of voluntary disclosure before and after the release of the 2013 IR framework can be used as a measure to determine if IR has had an impact on Malaysian voluntary disclosure. In a study by Jaffar, Nor and Selamat (2018), IR showed improvement in voluntary disclosure in three content elements, governance, strategy and resource allocation, and outlook. The rest of the content elements regressed compared to the levels before the release of the 2013 IR framework.…”
Section: Ir In Malaysiamentioning
confidence: 99%
“…<IR>'s overall quality remains low, failing to provide sufficient, comparable, material, and reliable information [30] [31] [32] [33]. For example, [31] argues that after adopting <IR>, organisations disclose more information on governance, resource allocation, and outlook, without considering the connectivity among the information. Reference [33] argues that <IR> practices have not achieved the expected level of transparency despite the increased level of disclosure.…”
Section: : Critiquesmentioning
confidence: 99%
“…Since the application of IRF in 2013, the authors have created their own binary coding systems to evaluate the quality of reporting based on this framework (Lee and Yeo, 2016; Zhou et al , 2017; Jaffar et al , 2018; Adegboyegun et al , 2020). Others have made use of existing evaluation sources such as the Ernst and Young (EY) Reports, Thompson Reuters Assets database and REBOCOSAM, Bloomberg, DataStream, etc.…”
Section: Synthesismentioning
confidence: 99%
“…Extant literature into the relationship between financial performance and the quality of non-financial reporting is segmented. Studies either focus on integrated reporting and performance, sustainability reporting and performance or corporate governance practices and performance (Garg, 2015; Lee and Yeo, 2016; Munshi and Dutta, 2016; Barth et al , 2017; Zhou et al , 2017; Jaffar et al , 2018). Additionally, the terms financial performance and financial sustainability are defined differently by authors, and the proxies used for assessing the quality of non-financial reporting are not standardised.…”
Section: Introductionmentioning
confidence: 99%